Microfinance - once and today - Reinhard H. Schmidt (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
The German savings and cooperative banks of the 19th century were precursors of modern microfinance. They provided access to financial services for the majority of the German population, which was formerly excluded from bank funding. Furthermore, they did this at low costs for themselves and affordable prices for their clients. By creating networks of financially viable and stable financial institutions covering the entire country, they contributed significantly to building a sound and "inclusive" financial infrastructure in Germany. A look back at the history of German savings and cooperative banks and combining these experiences with the lessons learned from modern microfinance can guide current policy and be valuable for present and future models of microfinance business.
urn:nbn:de:hebis:30:3-438846
Keywords: 330; Microfinance; German savings banks; German cooperative banks; Inclusive Finance